Linen Management in Laundry Installation of Undata General Hospital Palu - Norma Norma; Daswati Daswati; Nuraisyah Nuraisyah; Dandan Haryono; Abdul Rivai (Jurnal Syntax Admiration, 2023)
This Research aims to find out and analyze Linen Management in the Laundry Installation of the Undata Palu Regional General Hospital. The main theories that are referenced in this study are Terry's theory which includes; (1) Planning, (2) Organizing, (3) Actuating, (4) Controlling, This research method uses a descriptive - qualitative approach. The location of this research was located at the Laundry Installation of the Undata Palu Regional General Hospital, with 4 informants selected purposively. Data collection is carried out by conducting interviews, observations, and documentation. Data analysis techniques using Miles and Huberman interactive models. Based on the results of the research, Linen Management at the Laundry Installation of the Undata Palu Regional General Hospital is in the category of being able to be carried out according to the management process, that is from planning, organizing, mobilizing and supervising. Planning of work programs related to Linen in the Laundry Installation of the Undata Palu Regional General Hospital has been carried out according to the available budget both from direct and indirect sources of APBD, Organizing has not been implemented effectively by organizing human resources from recruitment to placement, Mobilization can be carried out by the leadership by directing or fostering employees to work appropriately and well, while supervision is carried out either directly or indirectly.